Protection of echium oil by microencapsulation with phenolic compounds. (October 2016) - Comunian, Talita A.; Boillon, Mickaël R.G.; Thomazini, Marcelo; Nogueira, Marina Sayuri; de Castro, Inar Alves; Favaro-Trindade, Carmen S.
Abstract: The consumption of omega-3 enables the reduction of cardiovascular disease risk; however they are unstable. The aim of this work was to encapsulate echium oil ( Echium plantagineum L.), a rich source of omega-3 fatty acids, with phenolic compounds (sinapic acid and rutin) by double emulsion followed by complex coacervation or by complex coacervation with sinapic acid in the capsule wall. Analyses of morphology, particle size, circularity, water activity, moisture, Fourier transform infrared spectroscopy, thermogravimetry, process yield, accelerated oxidation and identification and quantification of fatty acids present in the encapsulated oil were performed. Samples presented values of encapsulation process yield of phenolics and oil in the range of 39–80% and 73–99%, respectively. Moreover, all samples protected the oil against oxidation, obtaining induction time (accelerated oxidation) of 5 h for pure oil and values in the range from 10 to 18 h for samples. Thus, better protection to the oil was possible with sinapic acid applied in the capsule wall, which enhances its protection against lipid oxidation. Graphical abstract: Highlights: Coencapsulation of echium oil with phenolic compounds is viable. The action of sinapic acid as antioxidant was enhanced when applied in capsule wall. The capsules showed high yield of encapsulation process values for the oil. The encapsulation offered more stability to the echium oil.